Nurses’ knowledge, attitude and practice regarding postoperative pain management at selected hospitals, Bharatpur, Nepal - Thapa, Rupa Devi; Gurung, Ganga (Journal of Chitwan Medical College, 2020)
Background: Acute and severe pain after surgery is the major concern of operated patients and health professionals where the vital responsibilities goes to the nurses for managing pain satisfactorily. Hence, the nurses require to have adequate knowledge, attitude and practice (KAP) to carry out such responsibilities. Methods: A descriptive cross-sectional study design was used to find out the nurses’ KAP regarding postoperative pain (POP) management. Total 74 nurses of postoperative wards were selected from four hospitals at Bharatpur with non-probability enumerative sampling technique. Data were collected with the structured self-administered questionnaire for knowledge, five-point Likert scale for attitude and observation checklist for practice. Data were analyzed by using descriptive statistics for levels of KAP; Chi-square for association between levels of KAP with selected variables and spearman rank correlation to determine relationship among KAP regarding POP management. Results: The study showed that 85.1% nurses had low level of knowledge, 55.4% had satisfactory level of attitude and 52.7% had low level of practice. Statistically significant association was found between level of practice and age (p=0.010) of nurses and with professional qualification (p=0.002). There was no statistically significant relationship among KAP scores regarding POP management. Conclusions: Majority of the nurses had low level of knowledge, more than half had satisfactory level of attitude but low level of practice regarding POP management. The age and the professional qualifications of the nurses found to be associated with the practice of POP management.